EVALUATION OF SALES REVENUE IN TRADING BUSINESS - Margareta Yeni (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
The purpose of this research paper is to evaluate the business activities being conducted by business owners from the perspective of their sales revenue. The research method is descriptive qualitative, aiming to describe the actual conditions and circumstances of the business owners or research objects. Data collection methods were conducted using interviews and questionnaires. The results of this research paper indicate that business owners still lack understanding of how to evaluate their revenue, resulting in inaccurate information about the increases and decreases in revenue they experience due to the lack of continuous sales and revenue evaluation.